Antimicrobial Activity of Cladosporiumoxysporum Endophytic Fungus Extract Isolated From Aglaiaodorata Lour - Sugijanto, Noor Erma; Dorra, Bella Lexmita (Indonesian Journal of Medicine, 2016)
Background: Endophytic fungi have econoÃÂmiÃÂc potential as enzymes, medicines and biological control agents. Cladosporiumoxysporum endophytic fungi can be isolated from a plant named AglaiaÃÂoÃÂdorata Lour (Indonesian: Paca rCina). This plant can be found inPurwodadi Botanical Garden, PasuÃÂruan, East Java. This study aimed to assess the antimicrobial activity from the ethyl aceÃÂtate extract of the Cladosporiumoxysporum endophytic fungi against Escherichia coli, StaphyloÃÂcocÃÂcuÃÂsaureus, and Candida albicans.Subjects and Method: This was a descriptive study. C. oxysporum was cultivated, extracted, and fractionated. The fractions then were applied to antimicrobial activity assay. Disc diffusion method was used in this project with 2 mg/disc concentration extracts.Results: Some fractions of ethyl acetate extracts C. oxysporum showed antiÃÂmiÃÂcroÃÂbial activity against all microbials tested. 6 of 13 fractions exhibited inhibition zone against S. aureusATCC 6538, E. coli ATCC 8739, and C. albicansATCC 10231. The seventh fraction exhibited the highest inhibition zone against S. aureusATCC 6538, and C.albicans ATCC 10231.The tenth fraction exhibit ÃÂ ed the highest zone against E. coli ATCC 8739.Conclusion: CladosporiumoÃÂxysporum from Aglaiaodorata could be a good source of antiÃÂmicrobial substance.It produces bioactiveagent that can be developed into a new drug at a larger commercial scale.Keywords: endophytic fungi, cladosporiumn oxysporum, aglaiaodorata lour, antimicrobial activityCorrespondence:ÃÂ Noor Erma Sugijanto, Bella Lexmita Dorra. Faculty of Pharmacy, Airlangga University.Indonesian Journal of Medicine (2016), 1(2): 108-115https://doi.org/10.26911/theijmed.2016.01.02.04